Aplikasi Berbagai Dosis Pupuk UZAAKH dalam Menurunkan Kelarutan Logam Cr pada Tanah Sawah Tercemar Limbah Tekstil - Indra Permana; Mahfud Arifin; Rija Sudirja (Fakultas Pertanian Universitas Padjadjaran, 2018)
Degradation of rice field ecosystem by industrial waste contamination caused harmful impact for farming sustainability and crop production production. This study aimed to investigate the effect of various UZAAKH fertilizer dosage and its effect towards cation exchange capacity (CEC), pH, and Cr solubility reduction in contaminated rice fields from industrial waste. The experiment was conducted in the greenhouse of Agriculture Faculty Universitas Padjadjaran from April to September 2017. Randomized block design with six single treatments: A = UZAAKH 150 kg ha-1, B = UZAAKH 250 kg ha-1, C = UZAAKH 250 kg ha-1, D = UZAAKH 300 kg ha-1, E = UZAAKH 350 kg ha-1, dan F = Urea 200 kg ha-1, each treatment was replicated four times. The result showed that the application UZAAKH fertilizer has significant effect on CEC, pH, and Cr solubility on the soil. The dosage of 200 kg ha-1 UZAAKH fertilizer showed the highest CEC 60 day after application. UZAAKH fertilizer with 350 kg ha-1 dosage was the best dosage to increase soil pH and decrease Cr solubility application compared with other UZAAKH fertilizer dosage with the decrease of 69,05 % from initial concentration.Keywords: UZAAKH fertilizer, contaminated rice fields, heavy metal, Cr